DAMPAK PONSEL PADA KEHIDUPAN SPIRITUAL JEMAAT GBT KRISTUS PENEBUS SEMARANG - Stefany Yosephine Edrika; Hery Budi Yosef; Elizama Gulo; Adhi Siswanto Wisnu Nugroho (Jurnal Ilmiah Multidisiplin Ilmu, 2025)
This study aims to determine the impact of mobile phone use on the spiritual life of the GBT Kristus Peneburan Semarang congregation. This study uses quantitative and qualitative research methods with a sample of 50 respondents. The development of technology, especially smartphones, has had a significant impact on various aspects of life, including the spiritual life of Christians. This study aims to identify and analyze the impact of mobile phone use on the spiritual life of the congregation at the Bethel Tabernacle Church (GBT) of Christ the Redeemer Semarang. A qualitative approach was used with the methods of observation, interviews, and distributing questionnaires to a number of congregations. The results of the study show that mobile phones have a dual impact on the spiritual life of the congregation. On the one hand, mobile phones facilitate access to spiritual resources such as digital Bibles, online sermons, and virtual prayer groups, which can increase congregational engagement in religious activities, improving the ability to communicate with fellow congregations. On the other hand, excessive mobile phone use can disrupt the focus of worship, reduce direct social interaction, reduce time for prayer and Bible reading, increase the risk of dependence on technology and trigger spiritual distractions. This study also identified factors that affect the impact of mobile phones on the spiritual life of the GBT congregation of Christ the Redeemer Semarang, such as age, education level, and theological understanding. The implication of this study is the need to develop wise strategies in the use of mobile phones among the congregation with an emphasis on the use of technology to strengthen spiritual life and minimize its negative impacts.